Operational Strategy Analysis of Isolation Room Building and Observation of Covid-19 Patients Post-Pandemic at dr. Soegiri Hospital, Lamongan Regency, East Java - Itok Harimurti; Nugroho B; Fauziah Eddyono; Jamalullail (Jurnal Ilmu Multidisiplin, 2025)
The aim of this research is to formulate structural relationships related to the implementation of K3 in isolation and observation rooms for infectious diseases (covid 19) as well as to analyze operational strategies for building isolation and observation rooms after the Covid 19 pandemic at RSUD dr. Soegiri, Lamongan Regency, East Java. This research uses a qualitative descriptive method, in more detail the ISM used is descriptive statistical analysis. The research population was 15% of the workers at Dr Soegiri in the infectious disease room. In the ISM method, the respondents were decision makers, so 3 people were taken, namely the hospital director, head of the infectious diseases room and head of HSE. Based on the results above, this research shows that A1, which consists of measures to prevent transmission, breaking the chain of transmission, and increasing body resistance, is a key element or elements that have an influence on implementing the K3 program in the isolation room for Covid-19 patients at RSUD dr. Soegiri, Lamongan Regency.